Capital structure effect on firms performance: Focusing on consumers and industrials sectors of Malaysian firms / Zuraidah Ahmad, Norhasniza Mohd Hasan Abdullah and Shashazrina Roslan - Ahmad, Zuraidah; Mohd Hasan Abdullah, Norhasniza; Roslan, Shashazrina (2012)
This study seeks to investigate the impact of capital structure on firm performance by analyzing the relationship between operating performance of Malaysian firms, measured by return on asset (ROA) and return on equity (ROE) with short-term debt (STO), long-term debt (LTO) and total debt (TD). ). Four variables found by most literature to have an influence on firm operating performance, namely, size, asset grow, sales grow and efficiency, are used as control variables. This study covers two major sectors in Malaysian equity market which are the consumers and industrials sectors. 58 firms were identified as the sample firms and their financial data from the year 2005 through 2010 are used as observations for this study, resulting in a total numbers of observations of 358. A series of regression analysis were executed for each model, where either one of the capital structure proxies is included in each analysis. Lag values for the proxies were also used to replace the non lag values in order to ensure that any extended effect of capital structure on firm performance is also examined. The study finds that only short term debt and total debt has significant relationship with ROA while ROE has significant on the overall debt level. The analysis with lagged values shows that non of lagged values for total debt, short term debt and long term debt has significant relationship with performance. The study therefore concludes that capital structure has an effect on operating performance of Malaysian firms for two major sectors.